Explaining offline and online civic engagement intentions between Italian and migrant youth / Análisis de las intenciones de participación cívica virtual y presencial entre jóvenes italianos y emigrantes. Issue 2 (3rd May 2016) - Cicognani, Elvira; Albanesi, Cinzia; Mazzoni, Davide; Prati, Gabriele; Zani, Bruna
Abstract: The aim of the study was to assess the role of some psychosocial factors in explaining offline and online civic engagement intentions in a sample of Italian and second generation migrant (Albanian and Moroccan) adolescents and young adults living in Italy. The theoretical model was an extended version of the Theory of Planned Behaviour including past experience. The sample included 598 adolescents and young adults ( M = 19.32, SD = 3.17). Two hundred were Italian (88 males, 44.0%), 197 migrants of Albanian origin (130 males, 66%) and 201 migrants of Moroccan origin (116 males, 57.7%). Moroccan youth reported higher levels of both past civic engagement and future intentions than Albanian and Italian peers. Perceived effectiveness of civic engagement and past experience are consistently associated with stronger intentions to engage in the future (offline and online) in all groups. Internal efficacy plays a limited role, whereas the role of subjective norms differs according to the group and the source of normative influence (parents, peers).